Application of the Science Literacy Circles Method Based on Local Reality to Improve Students' Scientific Literacy - Nike Anggraini; Khoiron Nazip (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effectiveness of the Science Literacy Circles (SLC) method on students' scientific literacy skills. Research subjects are students of Biology education, FKIP UNSRI, who take an Introduction to Environmental Science course, Environmental Pollution material. This study uses a post-test-only control design. The students who were the samples in this study were taken using a purposive random sampling technique with the Indralaya class as the control class and the Palembang class as the experimental class, each with 1 class. The data analysis technique was carried out using an instrument sheet in the form of a test sheet. Based on the results of the study, it was shown that the experimental class had a higher achievement of scientific literacy skills than the control class in terms of several aspects of scientific literacy, namely aspects of competence, context, and attitudes towards science. The average percentage for the three aspects measured was obtained at an average of 69.03 for the control class and 82.88 for the experimental class.